2018
DOI: 10.1063/1.5057707
|View full text |Cite
|
Sign up to set email alerts
|

Reduced order derivation of the two-dimensional band structure of a mixed-mode resonator array

Abstract: In this paper, the 2D band structure of a mixed-mode metamaterial resonator array for in-plane waves is investigated. The band structure in the interior and on the boundary of the irreducible Brillouin zone as well as 1D dispersion diagrams for different propagation angles are calculated numerically and presented. Additionally, a reduced order analytical method is established to compare and approximate the band structure. The studied metamaterial, with a T-shaped cantilever beam as resonator in its square arra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The same is true for continuum FE models, which may lack symmetry due to their meshes. Another example can be found in 22 , where the direct FEM result suggests a real crossing between two branches, but the ROM and a further refined FEM study indicate otherwise. The ROM approach is more efficient for band sorting purposes (and can easily be leveraged in calculation of topological invariants based on path integrals), and it provides benefits in understanding the difference between an ideal model and a realistic one, as well as in distinguishing normal and accidental degeneracy.…”
Section: A Level Repulsion Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The same is true for continuum FE models, which may lack symmetry due to their meshes. Another example can be found in 22 , where the direct FEM result suggests a real crossing between two branches, but the ROM and a further refined FEM study indicate otherwise. The ROM approach is more efficient for band sorting purposes (and can easily be leveraged in calculation of topological invariants based on path integrals), and it provides benefits in understanding the difference between an ideal model and a realistic one, as well as in distinguishing normal and accidental degeneracy.…”
Section: A Level Repulsion Identificationmentioning
confidence: 99%
“…The materials are assumed to have no loss or gain mechanisms, but the inclusion of linear viscoelastic response is considered as a natural future expansion. Detailed numerical and experimental studies on some similar micro-structures can be found in previous work 21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation